(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ilhamdi ML, Idrus AA, Santoso D, Hadiprayitno G, Syazali M. 2021. The species richness and conservation priority of dragonflies in the Suranadi Ecotourism Area, Lombok, Indonesia. Biodiversitas 22: 1846-1852. Dragonflies are insects that have attractive colors and play an important role to balance ecosystems. They also act as bioindicators of the aquatic environment. The purpose of this study was to investigate the species richness and conservation priorities of dragonflies in the Suranadi Ecotourism Area, Lombok, Indonesia, expecting that the dragonflies will be used as charismatic species to support ecotourism. The research was conducted in August-December 2020 by surveying transect lines across 9 types of habitat. We then determined the conservation priority for each species found by referring to the Government Regulation using scoring method through a Focus Group Discussion (FGD) involving five experts. The score for each species was determined based on the percentage of the opinion from the experts. We found 18 dragonfly species from 2 suborders (Zygoptera and Anisoptera) and 5 families (Chlorocyphidae, Coenagrionidae, Platycnemididae, Aeshnidae and Libellulidae). The habitat type that supports the highest species richness was the waterway and irrigation (16 species), while the lowest species richness was found in the areas inside the forest habitat (2 species). The species that had the highest conservation priority scores were Pseudagrion pilidorsum declaratum, Libellago lineata, and Gynacantha subinterrupta. These three species can be used as conservation priority species in the ecotourism area of Suranadi, Lombok, Indonesia.